Transforming Vòdún : musical change and postcolonial healing in Benin's jazz and brass band music - Politz, Sarah (Musics in motion series., 2023)
Transforming Vòdún examines how musicians from the West African Republic of Benin transform Benin's cultural traditions, especially the ancestral spiritual practice of vòdún and its musical repertoires, as part of the process of healing postcolonial trauma through music and ritual. Based on fieldwork in Benin, France, and New York City, Sarah Politz uses historical ethnography, music analysis, and participant observation to examine three case studies of brass band and jazz musicians from Benin. The multi-sited nature of this study highlights the importance of mobility, and diasporic connections in musicians' professional lives, while grounding these connections in the particularities of the African continent, its histories, its people, and its present.